Spiritual machines: the merging of man and machine. - Kurzweil, Raymond (Futurist, 1999)
Computers will be inserted into clothes by 2009, will be embedded in the human body by 2019, and will have melded with human intelligence by 2099. The writer discusses the evolution of computers and their projected long-term impacts over the next century.